Regional convergence and economic development in the EU: the relation between national growth and regional disparities within the old and the new member states - Hans Kramar (European Regional Science Association (ERSA), 2015)
While European integration has substantially contributed to economic convergence between the member states of the EU, the diverging development of highly developed metropolitan regions and lagging rural areas has become a growing challenge especially for the new member states in Central and Eastern Europe. In this context the paper inquires to which degree the process of economic restructuring and catching-up in European countries was accompanied by increasing spatial disparities. Although a lot of research implicitly assumes that economically growing countries tend to face a trend towards increasing spatial inequalities, the question, whether there is a direct relation between total economic growth and spatial divergence, has not been answered sufficiently yet. The empirical investigation of regional and national GDP data confirms the trend towards economic convergence on a national scale between 2000 and 2011, mainly caused by the rapid growth of the most lagging countries. On a regional scale, however, the process of convergence was much slower and almost came to an end after the beginning of the global economic crises in 2008. The reason for these diverging results can be found in the change of disparities within the countries: While regional inequalities largely remained unchanged in the majority of the old member states, the gap between rich and poor regions widened in most countries which accessed the EU since 2004. This trend, however, slowed down or even reversed after 2008, which seems to confirm the assumption that economic growth intensifies spatial divergence. A detailed analysis of the correlation between national growth rates and the change of regional disparities, however, indicates that growing divergence in the new member states can hardly be explained by the speed of total economic growth, but rather has to be attributed to other specific conditions there. A reflection on the mechanisms of agglomeration economies suggests three arguments for the strong diverging effect of the catching-up processes in the new member states, which await to be tested empirically in future research.
Keywords: O; R; 330; regional disparities; convergence; cohesion policy